Tinjauan Yuridis terhadap Pengelolaan Dana Desa untuk Pengembangan Badan Usaha Milik Desa (BUMDes) di Desa Salo Timur Berdasarkan Undang-Undang Nomor 6 Tahun 2014 tentang Desa - Hafiz Sutrisno; Ratna Riyanti (PT PUSTAKA CENDEKIA GROUP, 2024)
This study aims to identify and analyze the implementation of Village Fund management in Salo Timur Village for the development of Village-Owned Enterprises (BUMDes) based on Law Number 6 of 2014 concerning Villages. The research employed an empirical juridical approach with a descriptive-analytical nature. Data were obtained through interviews with village officials, BUMDes managers, and analysis of legal documents and financial management reports. The results show that the management of Village Funds in Salo Timur Village adheres to the principles of transparency and accountability, although challenges remain in human resource capacity and business governance. It is necessary to enhance the competence of village apparatus and strengthen oversight systems to optimize the use of Village Funds in supporting economic independence through BUMDes.